Advertising on Trial - INGER L. STOLE (University of Illinois Press, 2006)
From its inception in the mid-nineteenth century, national advertising has evolved into a massive enterprise. In 2003, U.S. advertisers spent an estimated $236 billion, and today some scholars conclude that each day the average American is exposed to several thousand advertisements. By all accounts, advertising has saturated every nook and cranny of our lived experiences, bringing enormous social, cultural, and economic implications for this republic. Our media system is drenched in advertising and commercialism, yet these profit-driven enterprises are problematic for the democratic functioning of society and, some argue, for human happiness.1 And some Americans are unhappy. A 2004 study commissioned by the American Association of Advertising Agencies revealed a significant level of public dissatisfaction with advertising. Sixty-five percent of the respondents thought they were â€œconstantly bombarded with too much advertising,â€ 61 percent believed that advertising and marketing levels were â€œout of control,â€ and 60 percent of those interviewed said they currently held a more negative opinion of advertising than they had a few years ago. Nearly half the respondents reported that the excess advertising and marketing detracted from â€œthe experience of everyday life,â€ and 33 percent would be willing to settle for a slightly lower standard of living if this meant having a society devoid of marketing and advertising